THE POSITION OF WEALTH IN MARRIAGE BASED ON ISLAMIC PERSPECTIVES (KEDUDUKAN HARTA DALAM PERKAWINAN BERDASARKAN PERSPEKTIF ISLAM) - Mujani, Akhmad; Romdhoni, Abdul Aziz (Risâlah, Jurnal Pendidikan dan Studi Islam, 2019)
The article aims to describe the position of wealth in marriage based on an Islamic perspective. Islam is The comprehensive religion and regulates humans in various aspects of life, especially which related to property management. Property is the livelihood of every human being, whereas in order for this property to bring benefit to human life it must be managed based on Islamic principles. In the life of the nation and state, the management of property can be carried out based on two legal sides, namely Islamic high law and legislation regulations Artikel ini bertujuan untuk mendeskripsikan kedudukan harta dalam perkawinan berdasarkan perspektif Islam. Islam adalah agama yang komprehensif dan mengatur manusia dalam berbagai aspek kehidupan terutama yang berkaitan dengan pengelolaan harta. Harta merupakan mata pencaharian setiap manusia, namun supaya harta tersebut dapat membawa maslahat bagi kehidupan manusia harus dikelola berdasarkan prinsip-prinsip Islam. Dalam kehidupan berbangsa dan bernegara, pengelolaan harta benda dapat dilakukan berdasarkan dua sisi hukum yaitu hukum syariat Islam dan peraturan perundangan yang berlaku.